Evaluation of the Effect of Porcelain Laminate Thickness on Degree of Conversion of Light Cure and Dual Cure Resin Cements Using FTIR - Hoorizad Ganjkar, Maryam (J Dent (Shiraz), 2017)
STATEMENT OF THE PROBLEM: Increasing the thickness of the veneering porcelain may affect the polymerization of resin cements. Incomplete polymerization of resin cements can lead to compromised quality of restoration and decrease the longevity of indirect restorations. PURPOSE: This study sought to assess the effect of IPS Empress porcelain thickness on the degree of conversion of light-cure and dual-cure resin cements using Fourier transform infrared spectroscopy. MATERIALS AND METHOD: In this experimental study, IPS Empress porcelain discs (A2 shade) with 10mm diameter and 0.5, 1 and 1.5 mm thicknesses were fabricated. Choice2 (Bisco, USA) and Nexus3 (Kerr, USA) resin cements were light cured through the three porcelain thicknesses in two groups of 3 samples using a LED light-curing unit (LEDemetron II; Kerr, USA). The control group samples were cured individually with no porcelain disc. The degree of conversion of resin cements was determined using FTIR (Bruker; Equinox55, Germany). The data were analyzed using Dunn’s test. RESULTS: The degree of conversion (in percent) beneath the 0.5, 1.5 and 2 mm thicknesses of IPS Empress was 68.67±0.88, 71.06±0.94 and 72.51±0.41 for Choice2 resin cement and 69.60±2.12, 69.64±1.63 and 69.24±2.12 for Nexus3, respectively. Porcelain thickness and type of resin cement had no significant effect on degree of conversion (p≥ 0.05). CONCLUSION: It seems that increasing the porcelain thickness by up to 1.5 mm has no adverse effect on degree of conversion of both dual cure and light cure resin cements evaluated in this study.